2013
DOI: 10.1038/ncomms2394
|View full text |Cite
|
Sign up to set email alerts
|

A high-mobility two-dimensional electron gas at the spinel/perovskite interface of γ-Al2O3/SrTiO3

Abstract: The discovery of two-dimensional electron gases at the heterointerface between two insulating perovskite-type oxides, such as LaAlO 3 and SrTiO 3 , provides opportunities for a new generation of all-oxide electronic devices. Key challenges remain for achieving interfacial electron mobilities much beyond the current value of approximately 1,000 cm 2 V -1 s -1 (at low temperatures). Here we create a new type of two-dimensional electron gas at the heterointerface between SrTiO 3 and a spinel g-Al 2 O 3 epitaxial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
414
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(442 citation statements)
references
References 39 publications
25
414
2
1
Order By: Relevance
“…(2), we find a surprisingly high value m * = 5.6 m e . Considering the enhanced mobility of carriers in the WO 3 /LAO/STO system, in fact, one would expect a decreased effective mass, while in this case m * is three times larger than typical observations in LAO/STO heterostructures [17,35].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…(2), we find a surprisingly high value m * = 5.6 m e . Considering the enhanced mobility of carriers in the WO 3 /LAO/STO system, in fact, one would expect a decreased effective mass, while in this case m * is three times larger than typical observations in LAO/STO heterostructures [17,35].…”
mentioning
confidence: 65%
“…In order to promote high electron mobility, it is crucial to confine donor sites away from the conducting plane, without preventing the 2DES formation in the STO top layers. Previous attempts to control the defect concentration profile and thus enhance the mobility involved the use of crystalline insulating overlayers [14,15], adsorbates [16], amorphous materials [17] and even thin metallic layers [18,19]. A promising material to control defect formation is tungsten oxide WO 3 .…”
mentioning
confidence: 99%
“…24) results in lower carrier densities. Prior studies of 2DEGs in SrTiO 3 found upwards of 60%-95% of carriers in the 2DEG to not give rise to oscillations, 14,[31][32][33][34] which is likely due to disorder limiting the mobility of a significant fraction of the carriers, preventing oscillations to be resolved for all subbands.…”
Section: -mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27]31,32 Since this metallic layer results from the formation of oxygen vacancies near the interface, it characteristically vanishes with oxygen atmospheric annealing. [23][24][25][26][27] One such heterostructure is alumina/STO. Given the context of archetypical 2DEG LaAlO 3 /STO, where competing mechanisms 30 (including polar catastrophe, 10-15 cation exchange, 16,17 and oxygen vacancies [18][19][20][21][22][23][24][25][26][27] ) have been widely investigated and debated, the alumina/STO 2DEG offers an opportunity to isolate the role of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] Under certain conditions, it is energetically favorable for oxygen atoms near the interface to diffuse out of the STO during the initial stages of growth, stabilizing a confined conducting layer. [18][19][20][21][22][23][24][25][26][27]31,32 Since this metallic layer results from the formation of oxygen vacancies near the interface, it characteristically vanishes with oxygen atmospheric annealing. [23][24][25][26][27] One such heterostructure is alumina/STO.…”
Section: Introductionmentioning
confidence: 99%